PENGUATAN INTERPRETASI YURIDIS TERHADAP PASAL 85 UNDANG-UNDANG KEIMIGRASIAN: KAJIAN KETIDAKPASTIAN PELAKSANAAN PENGUPAYAAN PENDEPORTASIAN ORANG ASING DI INDONESIA - Rangga Adzani Bangsawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research examines the legal uncertainty in the enforcement of deportation efforts against foreign nationals as regulated under Article 85 of Law Number 6 of 2011 on Immigration. The legal norm contained in this article carries a formulation that is not entirely operational, thereby generating excessive discretion at the implementing level. This study employs a normative legal research method with a statute approach and a conceptual approach. Legal materials include immigration legislation, relevant court decisions, as well as doctrines of administrative law and international immigration law. The findings reveal that the normative construction of Article 85 has yet to provide adequate legal certainty regarding time limits, cross-agency coordination mechanisms, and the designation of responsible actors in deportation enforcement. The imprecision of the normative formulation results in impeded law enforcement against foreign nationals who violate immigration provisions. A strengthened juridical interpretation through systematic and teleological methods is warranted to provide a more certain legal foundation that can be consistently implemented by immigration officials.